PENGARUH PENGANGGURAN, KEMISKINAN DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN MIMIKA - Anif Hastin Fauziah; Abu Bakar (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to determine the effect of unemployment and poverty on the human development index in Mimika Regency. Data was obtained from the Mimika Central Statistics Agency (BPS). The data was analysed using an associative method and processed using SPSS software. The results of the analysis indicate that poverty has an effect on the human development index, while unemployment and economic growth have no effect on the human development index in Mimika Regency.